PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI THE JAYAKARTA SP JAKARTA HOTEL & SPA - Aris Budiono; Sigit Dani Nugroho; Shandyta Damara (Human Capital Development, 2020)
This study aimed to analyze the influence of leadership, compensation and motivation on employee performance at The Jayakarta SP Jakarta Hotel & Spa. The research was conducted at The Jayakarta SP Jakarta Hotel & Spa with a total of 80 respondents. The analysis method used is multiple regression. Based on the analysis and discussions, there is a significant positive influence of the motivation variable on employee performance. There is a significant positive effect of the compensation variable on employee performance. Simultaneously it was found that the influence of independent variables together on employee performance with a contribution of 41.7%, where other factors that influence but are not discussed in this study are 58.3. %